2017
DOI: 10.1038/ncb3466
|View full text |Cite|
|
Sign up to set email alerts
|

Long-range self-organization of cytoskeletal myosin II filament stacks

Abstract: Although myosin II filaments are known to exist in non-muscle cells, their dynamics and organization are incompletely understood. Here, we combined structured illumination microscopy with pharmacological and genetic perturbations, to study the process of actomyosin cytoskeleton self-organization into arcs and stress fibres. A striking feature of the myosin II filament organization was their 'registered' alignment into stacks, spanning up to several micrometres in the direction orthogonal to the parallel actin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
223
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(251 citation statements)
references
References 48 publications
25
223
2
1
Order By: Relevance
“…Since transverse deformations were never seen in experiments, it is clear that the stress fibres must be the predominant contractile elements observable at this resolution that respond to local RhoA-induced contractions. Furthermore, this result illustrates that it is appropriate to think of a stress fibre as a 1D contractile element with viscous and elastic components embedded in a passive viscoelastic network, which is consistent with recently published image-based observations26.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Since transverse deformations were never seen in experiments, it is clear that the stress fibres must be the predominant contractile elements observable at this resolution that respond to local RhoA-induced contractions. Furthermore, this result illustrates that it is appropriate to think of a stress fibre as a 1D contractile element with viscous and elastic components embedded in a passive viscoelastic network, which is consistent with recently published image-based observations26.…”
Section: Resultssupporting
confidence: 91%
“…In contrast, at longer timescales, it is thought that dynamic processes make the cytoskeleton behave predominately like a viscous fluid, enabling cytoskeletal flows and remodelling. These dynamic processes, including exchange of proteins from the cytosol, are typically on the order of tens of seconds in structures like the cortex2425 and on the order of a minute in stress fibres26. The molecular regulation underlying the competition between elastic and viscous processes in cells is not well understood.…”
mentioning
confidence: 99%
“…Recent research, using superresolution light-microscopic imaging of living cells by which individual myosin filaments could be discerned, have shown that myosin filaments are very dynamic (32)(33)(34). Myosins tagged with fluorescent fusion proteins were imaged as closely spaced "dumbbells" corresponding to the ∼300-nm-long bipolar filaments assembled in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics underlying changes in NMII reorganization are just beginning to be understood (Beach et al, 2017;Hu et al, 2017). EMT, the process by which static, well-ordered and apical-basal polarized epithelial cells transform into dynamically migrating mesenchymal cells associated with extensive reorganization of the actomyosin cytoskeleton is of major interest and is important for cardiac development.…”
Section: Nmiib Function In Myocardial Growthmentioning
confidence: 99%